Evaluation the effect of burning investment and black sand materials on the surface roughness of acrylic resin denture base - jaber, Makarem (Iraqi National Journal of Nursing Specialties, 2012)
Objective: The aim of this study was to evaluate the effect of pumice, burning investment material and black sand on the surface roughness of heat cure acrylic resin. Methodology: Sixty specimens were prepared from pink heat cure acrylic resin, the specimens where grouped into; 20 specimens which polished with pumice and water (control group); 20 specimens which polished with investment material (after burning it) and water; and 20 specimens which polished with black sand and water. The average surface roughness of specimens after polishing procedure had been determined by profilometer (surface roughness tester). Results: Through the application of ANOVA and LSD tests, the result of this study showed that there was a highly significant difference among the three groups at (P<0.001). Recommendation: it may be concluded that the smoother surface of specimens gained by burning investment material was significantly higher than that of black sand and pumice materials. So that burning investment material can be used as a polishing material for heat cure acrylic resin denture base instead of pumice material.